Efektivitas Layanan E-Samsat Pajak Kendaraan Bermotor di Wilayah Surabaya Timur - Maharani, Della Sabrina; Fanida, Eva Hany (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The utilization of information technology in public services is part of the implementation of e-government to achieve efficient and responsive governance. One such innovation is E-Samsat, a digital system for motor vehicle tax payments. In East Surabaya Samsat, although tax revenue through E-Samsat increased in 2023–2024, its contribution remains relatively low compared to the total motor vehicle tax revenue. This indicates that public adoption of E-Samsat services is still limited. Therefore, this study aims to evaluate the effectiveness of E-Samsat as a digital payment system for motor vehicle taxes at East Surabaya Samsat. A descriptive qualitative method was used. Data were collected through documentation and semi-structured interviews, and analyzed using the interactive model by Miles and Huberman. Service effectiveness was assessed using eight indicators proposed by Pedrosa et al. (2020): ease of use, usefulness, simplicity, reliability, availability, understandability, consistency, and speed. The findings show that E-Samsat is technically and functionally effective in improving service efficiency. However, obstacles such as low public understanding, lack of socialization, and uneven digital infrastructure still hinder the system’s optimal performance. This study recommends strengthening digital education, expanding technology access, and continuously improving service quality to ensure that E-Samsat functions effectively as an inclusive digital public service solution.